Anaphylaxis caused by stings from the Solenopsis invicta, lava-pés ant or red imported fire ant - Haddad Junior, Vidal [UNESP]; Larsson, Carlos Eduardo (FapUNIFESP (SciELO), 2015)
Ants are social insects with species of medical interest, such as the fire ants (Solenopsis sp.). The sting causes inflammation, vesicles and sterile pustules, which may cause allergic phenomena and even anaphylactic shock. We describe a patient who suffered a large number of stings and an episode of syncope with fall in blood pressure and complete regression of symptoms after resuscitation and medication for anaphylaxis. Considering the clinical manifestations and images of wheals and blisters on the patient's feet at the time of syncope, this report should serve as a warning for the diagnosis and treatment of this condition and even for counseling and prevention regarding patients exposed to this risk.
Keywords: Anaphylaxis; Ant venoms; Ants; Brazil; Immediate hypersensitivity